Advanced mucinous colorectal carcinoma in a 14-year old male child: A case report and review of the literature. (2020) - Mremi, Alex; Yahaya, James J.
Highlights: Colorectal carcinoma in children is extremely rare and it carries poor prognosis. Diagnosis of this malignancy in children usually is done at advanced stages. Mucinous variant is the most common histological type of colorectal cancer in children. Screening for colorectal cancer in children helps to diagnose the disease at early stage. Abstract: Introduction: ColorectaI carcinoma is extremely rare in children and presents with a poor prognosis. Presentation of case: The present report describes the case of a 14-year old male child who presented with complaints of general weakness and recurrent abdominal pain, caused by a mucinous adenocarcinoma of the transverse colon (Dukes stage which was inoperable. Discussion: Mucinous histopathological type is the most common type with increased ability to invade the adjacent stromal tissue. This biological behaviour has been reported to be attributable to its aggressive behaviour. Additionally, delay of diagnosis of colorectal carcinoma in children accounts for the advanced disease at diagnosis. Conclusion: Colorectal carcinoma occurring in both children and adolescents usually have poor prognosis because of not having specific symptoms which contributes to delay of diagnosis. Mimicking of its symptoms with other non-malignant conditions such as intestinal obstruction and acute appendicitis also has been found to contribute to delay of diagnosis as it was in our present case.